UPAYA PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN DALAM PENANGGULANGAN TINDAK PIDANA PENCUCIAN UANG - Eko Raharjo (Universitas Lampung, 2007)
The issue of crime not only from the public spotlight in the local and national level, but also a serious concern of the international community. One crime that is now often used as a discussion by scholars of law, economics and banking apparatus of government and law enforcement are on the money laundering crime (money laundering), especially with the notion that the Republic of Indonesia is